Effects of Early Life Experiences on Brain Development of Premature Babies Admitted in Neonatal Intensive Care Unit - Ali Hirani, Shela Akbar (International Journal of Pediatrics and Child Health, 2013)
Infancy is the most crucial time period in children’s life during which babies require sensitive and responsive care-giving from their primary caregivers for their overall growth and development. Sick preterm babies, who require admission at Neonatal Intensive Care Unit (NICU) and experience physical separation from their parents during early days of their lives, are at high risk to encounter toxic stress that can be detrimental for their developing brains, overall development and stress regulatory mechanism in later life. This paper presents case study of a preterm baby who encountered toxic stress due to the effects of disease process, physical separation from primary caregivers, painful procedures at NICU, as well as bright and noisy environment of NICU. In the light of the presented case study and reviewed literature, modifications in the NICU environment are suggested to reduce the sources of toxic stress on the developing brains of premature babies. Role of lactation support for mothers of preterm babies, kangaroo mother care, and neurodevelopmental care in the NICU environment is highlighted to assure growth promotion, brain development, infant-mother bonding, and better cognitive functions among premature babies.